Detection of summer truffle (Tuber aestivum Vittad.) in ectomycorrhizae and in soil using specific primers - Gryndler, Milan; Hršelová, Hana; Soukupová, Lucie; Streiblová, Eva; Valda, Slavomír; Borovička, Jan; Gryndlerová, Hana; Gažo, Ján; Miko, Marián (FEMS microbiology letters, 2011)
Tuber aestivum is becoming an important commodity of great economical value in some European countries. At the same time, it is a highly protected organism in other countries, where it needs careful treatment. A reliable method of detection in roots and soil is thus needed for assessment of geographic distribution, ecological studies and inoculation efficiency testing in man-made experiments. A PCR-based method of detection of T. aestivum using specific primers was therefore developed. A pair of PCR primers Tu1sekvF/Tu2sekvR selective for T. aestivum and some genotypes of Tuber mesentericum was designed on the basis of the known internal transcribed spacer T. aestivum sequences. TaiI restriction cleavage was then used to distinguish the two species. The selectivity of the designed primer pair was evaluated using DNA extracted from specimens of a further 13 Tuber spp. Subsequently, the selectivity and robustness to false-positive results with nontarget DNA of the designed primers was compared with two other primer pairs (UncI/UncII and BTAE-F/BTAEMB-R). The occurrence of T. aestivum in soil and ectomycorrhizae collected in its native habitat has been successfully detected using the designed primers and nested PCR. The method is reliable and thus suitable for detection of T. aestivum in the field.
Keywords: půdní mikrobiologie; Soil Microbiology; Molecular Sequence Data; DNA primery; mykorhiza; DNA Primers; Ascomycota; molekulární sekvence - údaje; Mycorrhizae; Polymerase Chain Reaction; polymerázová řetězová reakce